Preparação de copolímeros PEG-PCL modificado com ácido fólico para liberação controlada de metotrexato - Brandt, João Victor [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Several drugs have low solubility within the human body, decreasing its bioavailability. Currently, several liberation platforms have been studied in order to overcome this limitation. Among the carriers employed, functionalized block copolymers have the advantage of interacting with the drug both hydrophilic and hydrophobically. Thus, the study of these platforms is fundamental for the encapsulation of hydrophobic drugs, allowing a greater time of circulation in the organism. The efficiency of incorporation and controlled release is dependent on the size, morphology and interactions of the copolymer blocks. The study focused on the physico-chemical properties of these materials (colloidal stability and micelle size, polymer chain length and micelle-drug affinity) in order to obtain better incorporation results. The use of these carriers is promising in the development of drug delivery systems. The reduction of the side effects, due to the use of these carriers, will allow the patient a less aggressive and more efficient treatment, improving the quality of life. In this work, the formation of micelles of PEG-co-PCL diblock copolymers with and without folic acid functionalization with varying chain size was evaluated and the efficiency of methotrexate incorporation was evaluated. The synthetic method, in which the monomers were added in the presence of catalyst in an inert atmosphere to a round bottom flask, allowed obtainingsamples with low polydispersity index. The samples were characterized by several techniques, such as: infrared transmittance spectroscopy, proton nuclear magnetic resonance spectroscopy, gel permeation chromatography, thermogravimetry, differential scanning calorimetry andX-ray diffraction. The micellar stability determined from the influence of the pH and temperature on the zeta potential and the hydrodynamic diameter of the micelles, in which the micelles were not influenced by temperature and added at pH values close to 4...

Diversos fármacos apresentam baixa solubilidade dentro do corpo humano, diminuindo sua biodisponibilidade. Atualmente, diversas plataformas de liberação vêm sendo estudadas a fim de superar tal limitação. Entre os carreadores empregados, os copolímeros em bloco funcionalizados apresentam a vantagem de interagirem com o fármaco tanto hidrofílica quanto hidrofobicamente. Dessa forma, oestudo destas plataformas é fundamental para o encapsulamento de fármacos hidrofóbicos, permitindo um maior tempo de circulação no organismo. A eficiência de incorporação e liberação controlada é dependente do tamanho, morfologia e das interações dos blocos de copolímeros.O estudo se concentrou nas propriedades físico-químicas destes materiais (estabilidade coloidal e tamanho das micelas, tamanho de cadeia polimérica e afinidade micela-fármaco) com a finalidade de obter melhores resultados de incorporação.O uso destes carreadores é promissor no desenvolvimento de sistemas de liberação de fármacos. A diminuição dos efeitos colaterais, em função do uso destes carreadores, permitirá ao paciente um tratamento menos agressivo e mais eficiente, melhorando a qualidade de vida. Neste trabalho, avaliou-se a formação de micelas de copolímeros dibloco PEG-co-PCLcom e sem funcionalizaçãocom ácido fólicocom variado tamanho de cadeia e avaliou-se a eficiência de incorporação demetotrexato.O método sintético, no qual foramadicionados os monômeros na presença de catalisador em atmosfera inerte aum balão de fundo redondo, permitiu a obtenção de amostras com baixo índice de polidispersão. As amostras foram caracterizadas por diversas técnicas, tais como: espectroscopia de transmitância na região do infravermelho, espectroscopia de ressonância magnética nuclear de próton, cromatografia de permeação em gel, termogravimetria, calorimetria exploratória diferencialedifração de raios-X. A estabilidade micelar determinada...
Keywords: Tecnologia de liberação controlada; Copolímeros bloco; Micelas; Fármacos; Metotrexato; Block copolymers